Direct detection of ESKAPEc pathogens from whole blood using the T2Bacteria Panel allows early antimicrobial stewardship intervention in patients with sepsis - Drevinek, Pavel; Hurych, Jakub; Antuskova, Milena; Tkadlec, Jan; Berousek, Jan; Prikrylova, Zuzana; Bures, Jiri; Vajter, Jaromir; Soucek, Martin; Masopust, Jan; Martinkova, Vendula; Adamkova, Jaroslava; et al. (MicrobiologyOpen, 2021)
In the microbiological diagnosis of bloodstream infections (BSI), blood culture (BC) is considered the gold standard test despite its limitations such as low sensitivity and slow turnaround time. A new FDA-cleared and CE-marked platform utilizing magnetic resonance to detect amplified DNA of the six most common and/or problematic BSI pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Escherichia coli; referred to as ESKAPEc) is available and may shorten the time to diagnosis and potentially improve antimicrobial utilization. Whole blood samples from hospitalized patients with clinical signs of sepsis were analyzed using the T2Bacteria Panel (T2Biosystems) and compared to simultaneously collected BC. Discrepant results were evaluated based on clinical infection criteria, combining supporting culture results and the opinion of treating physicians. A total of 55 samples from 53 patients were evaluated. The sensitivity and specificity of the T2Bacteria panel was 94% (16 out of 17 detections of T2Bacteria-targeted organisms) and 100%, respectively, with 36.4% (8 of 22) causes of BSI detected only by this method. The T2Bacteria Panel detected pathogens on average 55 hours faster than standard BC. In our study, 9 of 15 patients with positive T2Bacteria Panel results received early-targeted antibiotic therapy and/or modification of antimicrobial treatment based on T2Bacteria Panel findings. Given the high reliability, faster time to detection, and easy workflow, the technique qualifies as a point-of-care testing approach.
Keywords: Staphylococcus aureus; kultivační vyšetření krve; Antimicrobial Stewardship; Blood Culture; antibakteriální látky; Klebsiella pneumoniae; Prospective Studies; antibiotická politika; Escherichia coli; Acinetobacter baumannii; Enterococcus faecium; Blood; lidé; Pseudomonas aeruginosa; Anti-Bacterial Agents; Humans; bakteriemie; Bacteremia; krev; prospektivní studie